Fabulous Scarves / Sharifah Nur Izzah Ilyana Syed Abdul Halim…[et al.]. - Syed Abdul Halim, Sharifah Nur Izzah Ilyana; Azizan, Nur Nadiah Nadirah; Hazuki, Nur Syamimie; Mohd Juhari, Nur Anis Zulaikha; Hazri, Faiz Afrina (2021)
Fabulous Scarves company is a form of business based on a partnership that consists of five members and each holds important positions which is General Manager, Administration Manager, Marketing Manager, Operation Manager, and Financial Manager. Each position needs to play an important role in the company to achieve the targets set by the company manager. The business capital amounts to RM100,000 where the contribution of each member is RM20,000. Our company provide various type of scarves such as Plain Shawl, Plain Bawal, Pleated Shawl, Printed Shawl and Printed Bawal which provides a very comfortable fabric for our consumers, not sparse, not easily wrinkled and has a variety of attractive colors and patterns at an affordable price. Furthermore, Fabulous Scarves company with the motto of “Be Bold, Be Beautiful” is located at Ampang Selangor with the address: Jalan UP 8/9, Ukay Perdana 3, Avenue Ampang, 68000 Ampang Selangor. Our company will focus on quality fabric types because it is the first thing that customers will evaluate, whether the fabric is comfortable or not for them to consume. In addition, the patterns we choose are also the best among the best because we want the quality and variety to move in tandem to produce something different from other scarves out there. To make it more attractive we decided to make some innovation by present something different. We have done some research about the problem of women who wearing hijab and among them is that they have the problem of damaged hair when wearing the hijab for too long, so we decided to provide a hijab that can help reduce hair problems such as hair will not easily damage, hair loss problems, itchy scalp, and dandruff problems.